2011
DOI: 10.1371/journal.pone.0018322
|View full text |Cite
|
Sign up to set email alerts
|

IL28B SNP rs12979860 Is a Critical Predictor for On-Treatment and Sustained Virologic Response in Patients with Hepatitis C Virus Genotype-1 Infection

Abstract: BackgroundSingle nucleotide polymorphisms (SNPs) of interleukin-28B (IL28B) have received considerable interest for their association with sustained virological response (SVR) when treating patients of genotype-1 hepatitis C virus (GT1-HCV) chronic infection with pegylated interferon and ribavirin (PegIFN/RBV). This study was to investigate the predictive power of IL28B SNPs for on-treatment responses and SVR in treatment-naïve patients with GT1-HCV chronic infection.Methodology/Principal FindingsWe analyzed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
62
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 43 publications
10
62
0
1
Order By: Relevance
“…The current study was the first to investigate a large number of Brazilian patients and the frequency of the C allele was assessed in a cohort of 263 patients with liver fibrosis due to infection with HCV genotype 1. The C allele was present in 39% of patients, which is lower than the frequencies reported from Europe, Asia and Oceania, but similar to that observed in Africa (IBGE 2000, Thomas et al 2009, Lin et al 2011, and this finding may be due to the large proportion of African descendants in the Brazilian population. The present study confirmed that the IL28B polymorphism is a good predictor of SVR, independent of other factors, such as age, gender, stage of liver fibrosis and VL.…”
Section: Discussionsupporting
confidence: 58%
“…The current study was the first to investigate a large number of Brazilian patients and the frequency of the C allele was assessed in a cohort of 263 patients with liver fibrosis due to infection with HCV genotype 1. The C allele was present in 39% of patients, which is lower than the frequencies reported from Europe, Asia and Oceania, but similar to that observed in Africa (IBGE 2000, Thomas et al 2009, Lin et al 2011, and this finding may be due to the large proportion of African descendants in the Brazilian population. The present study confirmed that the IL28B polymorphism is a good predictor of SVR, independent of other factors, such as age, gender, stage of liver fibrosis and VL.…”
Section: Discussionsupporting
confidence: 58%
“…93 In East Asian HCV-1 patients who received 24 weeks of PEG-IFN α-2a plus RBV therapy, the IL-28B genotypes played a minor role to affect the overall SVR rates if they achieved RVR. 80,94,95 In line with the report by Thompson et al, IL-28B genotypes strongly affected the SVR rates in East Asian HCV-1 patients if they failed to achieve RVR. 96,98 However, the role of IL-28B genotypes was limited in East Asian HCV-1 patients who failed to achieve RVR if Wk-8R was taken into consideration.…”
Section: Impact Of Interleukin-28b Genotype On Viral Responses In Asisupporting
confidence: 68%
“…91,92 Furthermore, IL-28B genotypes are associated with the RVR rates in HCV-infected patients, especially in those with HCV-1 infection. 78,80,91,[93][94][95][96][97] Because the favorable IL-28 genotype highly predicts RVR and SVR in HCV-1 patients, Asian HCV-1 patients, who carry the highest frequency of the favorable IL-28B genotype, have greater SVR rates than HCV-1 patients of other ethnicities.…”
Section: Impact Of Interleukin-28b Genotype On Viral Responses In Asimentioning
confidence: 99%
“…4 Moreover, IL-28B gene polymorphisms were the strongest predictors of response to pegylated interferon and RBV in patients chronically infected with HCV genotypes 1 and 4. 5 Some studies found that the protective rs12979860 C allele frequency was 91.0%-97.5% in east Asia population, which may be the possible reason why domestic patients had a higher SVR than aboard. Therefore, therapy of CHC recently entered a new era with the deployment of direct-acting antivirals (DAAs), and IL-28B genotyping will be also useful for personalized CHC treatment in the forthcoming era of DAAs.…”
Section: Discussionmentioning
confidence: 99%